Manajemen Pembinaan Peserta Didik pada Lembaga Pendidikan - Amelia Amelia; Arimbi Syahkila Simangunsong; Rizki Akmalia; Sylvi Marsella Diastami; Syahfitri Halawa; Amaluddin Tanjung (Journal on Education, 2023)
This article aims to find out and analyze the management of students in educational institutions. This paper examines the management of students in educational institutions. This article method uses the literature study method which relies on data sourced from books, articles in scientific journals related to the subject matter. Management is a process that contributes to individuals and groups understanding how to manage things, just like managing students. Thus the management of students in educational institutions is a process for managing students in order to achieve predetermined educational goals. And those who manage these students are educational institutions (schools) and educators in these educational institutions.